Determination of Water-Soluble Vitamins in Palmyrah Sweet Sap and Its Derived Products using RP-HPLC Method - Thangavel, Kirushanthi; Arumugam, Mithursha; Anuluxshy, Balasubramaniyam; Sajiwanie, J.W.Amadnda; Srivijeindran, Srithayalan (Food, Agriculture and Natural Resources - NETWORKS, 2024)
Palmyrah sweet sap, obtained from the inflorescence of the Borassus flabellifer L. palm tree, is a popular natural drink in Sri Lanka, available seasonally from January to August. It contains a blend of water, sugars, and essential vitamins and minerals. The sweet sap is processed thermally to produce sugary products like crude sugar, jaggery, and treacle. It is crucial to analyze them to ensure their nutritional value, due to the possibility of vitamin decomposition during the production stage. This study aimed to quantify the existing vitamins in sweet sap and its derived products using validated high-performance liquid chromatography (HPLC). The HPLC method validation parameters, such as linearity, accuracy, precision, range, limit of detection (LOD), and limit of quantification (LOQ), were determined. The results showed that the derived products from palmyrah sap had high concentrations of vitamins, with thiamine ranging from 2.81 to 35.16 mg/100g, niacin from 4.35 to 45.03 mg/100g, pyridoxine from 4.44 to 87.16 mg/100g, and ascorbic acid from 5.42 to 52.52 mg/100g. The accuracy of the HPLC method for vitamin analysis was between 98.43 and 100.64%, with a limit of detection ranging from 0.357 to 1.152 ppm and a limit of quantification from 1.081 to 13.573 ppm. The study successfully quantified the existing vitamins in the sap and its derived products, with overall results indicating that the vitamins were retained even after thermal processing.